Deep Learning as a Transformative Approach to Social Studies Education - Kamaruddin, Kamaruddin; Saqjuddin, Saqjuddin (International Journal of Management and Education in Human Development, 2025)
The deep learning approach is increasingly relevant in addressing the needs of 21st-century education, which demands the development of critical thinking skills, conceptual understanding, and emotional engagement in the learning process. This article aims to systematically examine the potential of deep learning as a transformative approach in Social Studies (IPS) education in elementary schools. Using a literature review method, this article analyses more than 30 academic sources published over the past five years that discuss the concepts, models, practices, and challenges of implementing deep learning in social studies. The study results indicate that this approach can improve students' reflective thinking skills, social awareness, and empathy for local and global issues. Deep learning also encourages a transformation of the teaching paradigm to make it more participatory and student-centered..However, the implementation of this approach still faces obstacles such as limited teacher understanding, rigid curriculum structures, and minimal resource support. Recommended strategies include practice-based teacher training, flexible curriculum development, and the creation of a collaborative and reflective school ecosystem. Learning social studies with an immersive approach impacts content mastery and shapes students' character as active, inclusive, and responsible citizens. Therefore, in-depth learning is a strategic approach to realising the transformative and contextual goals of social studies education within the framework of the Independent Curriculum.